Probiotics and antimicrobial protein and peptide levels in preterm infants. (18th April 2017) - Strunk, Tobias; Hibbert, Julie; Doherty, Dorota; Granland, Caitlyn; Trend, Stephanie; Simmer, Karen; Burgner, David; Patole, Sanjay; Currie, Andrew
Abstract: Aim: To characterise the secreted and inducible antimicrobial protein and peptide (APP) levels in a prospective cohort of preterm infants (<30 weeks gestational age) with or without Bifidobacterium breve M16V supplementation during the first month of life. Methods: We analysed serial biosamples of infants who did (n = 13) or did not receive (n = 62) B. breve (3 × 10 9 cfu/day). Peripheral blood was obtained on days 1, 14 and 28, and infant stool prior to commencement of probiotic supplementation and on day 21. Levels of APP (bactericidal/permeability inducing protein (BPI), beta defensins 1 and 2, lactoferrin, human cathelicidin, secretory phospholipase A2) in plasma and stool were determined. Further, we characterised induced APP levels in whole blood cultured with live S. epidermidis or with agonists of Toll‐like receptors 2/6 and 4. Results: Stool, plasma and stimulated blood APP levels changed significantly during the first month of life. Supplementation with B. breve did not affect basal or stimulated APP levels except for a transient increase in inducible BPI. Conclusion: Supplementation with B. breve does not appear to act via modulation of systemic or enteric APP expression in preterm infants although small effects cannot be excluded. Further work with other probiotic preparations is warranted.